Asymmetric passive components in microwave integrated circuits - Ahn, Hee-Ran (J. Wiley & Sons, 2006)
This book examines the new and important technology of asymmetric passive components for miniaturized microwave passive circuits. The asymmetric design methods and ideas set forth by the author are groundbreaking and have not been treated in previous works. Readers discover how these design methods reduce the circuit size of microwave integrated circuits and are also critical to reducing the cost of equipment such as cellular phones, radars, antennas, automobiles, and robots.